The Great Forest An Appalachian Story - Buxton, Barry; Gray, Sam (Appalachian State University, 1985)
The very ancient Eastern forest of North America is characterized by an extraordinary variety of plants, animals, and human communities. Published in 1985 and edited by Barry M. Buxton (1st edition) and Sam Gray (2nd edition), contributors to A Great Forest: An Appalachian Story, include Sam Gray and Michael Ann Williams; Ann Rogers; Tyler Blethen and Curtis Wood; Ronald D. Eller; and Harley E. Jolley. The writings examine the natural and cultural landscape of the Appalachian region, and provides a detailed history of the area. In order to study the ecology of the forest, a narrative of the people behind the forest and how they have impacted and changed the landscape is included.